Association of the European Lactase Persistence Variant (LCT-13910 C>T Polymorphism) with Obesity in the Canary Islands - Almon, Ricardo; Álvarez-León, Eva Elisa; Serra-Majem, Lluís (PloS one, 2012)
European lactose tolerance genotype (LCT -13910 C>T, rs4988234) has been positively associated to body mass indexes (BMI) in a meta-analysis of 31,720 individuals of northern and central European descent. A strong association of lactase persistence (LP) with BMI and obesity has also been traced in a Spanish Mediterranean population. The aim of this study was to analyze a potential association of LP compared to lactase non-persistence (LNP) with BMI in inhabitants of the Canary Islands of Spain using Mendelian randomization. A representative, randomly sampled population of adults belonging to the Canary Islands Nutrition Survey (ENCA) in Spain, aged 18-75 years (n = 551), was genotyped for the LCT - 13910 C>T polymorphism. Milk consumption was assessed by a validated questionnaire. Anthropometric variables were directly measured. WHO classification of BMI was used. LP individuals were significantly more obese than LNP subjects (χ(2) = 10.59; p<0.005). LP showed in a multivariate linear regression analysis showed a positive association of LP with BMI compared to LNP, (β = 0.96; 95% CI: 0.08-1.85, p = 0.033). In a multinomial logistic regression analysis normal range weight LP subjects showed an odds ratio for obesity of 2.41; 95%CI 1.39-418, (p = 0.002) compared to LNP. The T-13910 of the allele LCT-13910 C>T polymorphism is positively associated with BMI. LP increases significantly the risk to develop obesity in the studied population. The LCT-13910 C>T polymorphism stands proxy for the lifetime exposure pattern, milk intake, that may increase susceptibility to obesity and to obesity related pathologies.